(untitled) (Czech Journal of International Relations, 2023)
Europa Universalis IV, (better known as EUIV), is a popular grand strategy PC game. Players choose a country to play as and start in the year 1444 with the option to plot new courses in history such as allowing players to form Ruthenia, the game’s version of Ukraine. In this article, I investigate how both Ukrainian and non-Ukrainian online content creators have been making content related to Ruthenia and Ukraine as a response to Russia’s February 2022 invasion of Ukraine. I highlight how this content allows creators and viewers to voice their opinions on the war, build a sense of solidarity with the Ukrainian military, debate issues related to the war, and raise money for Ukrainians in need. Through close readings of this content, I offer an analysis of how this community uses the game to build a "vernacular geopolitics" in which information about and understandings of international relations and conflicts develop in non-elite settings.